Effects of Bacillus subtilis ZY1 on production performance, egg quality, serum parameters and intestinal health in laying hens - Rongrong Dong; Hao Liu; Huan Zhang; Fengyang Wu; Haidong Xiu; Shiwei Chen; Xinxiang Yin; Xiaohui Zhou (Poultry Science)
To evaluate the effects of Bacillus subtilis ZY1 supplementation, production performance, egg quality, serum parameters, and intestinal health in laying hens were investigated. A total of 240 healthy 59-week-old Hy-Line Brown laying hens were randomly assigned to four groups: a control group (Con) fed a basal diet and three treatment groups supplemented with Bacillus subtilis ZY1 at levels of 0.05 % (LG), 0.1 % (MG), and 0.2 % (HG). The duration of trial lasted eleven weeks, including a one-week pre-feeding phase. The results indicated that dietary supplementation with ZY1 increased the egg laying rate in the LG and HG groups (P < 0.05) as well as improved the qualified egg rate in the LG and MG groups (P < 0.05). Moreover, the LG group also demonstrated superior egg quality and enhanced antioxidant capacity and immune function by decreasing the level of MDA (42.47 %) and improving the content of T-AOC, GSH-Px, CAT, SOD, IgM and IgG (34.31 %, 23.92 %, 37.68 %, 31.64 %, 14.01 %, and 17.84 %, respectively) in serum samples (P < 0.05). The changes in biochemical parameters such as AST, LDH, TG (12.40 %, 13.79 %, and 32.13 % decreased, respectively) and Ca (41.35 % increased) were particularly pronounced in LG groups (P < 0.05), indicating that ZY1 supplementation enhanced metabolic capacity of laying hens (P < 0.05). Furthermore, laying hens in the treatment groups exhibited significantly increased villus height (VH) and an elevated villus height-to-crypt depth ratio (VH/CD) within their duodenal tissues (P < 0.05). These findings suggest that dietary supplementation with ZY1 effectively improves production performance, egg quality, serum parameters, and intestinal health in laying hens; notably, a dosage of 0.05 % ZY1 was identified as the optimal level for these improvements. This study provides valuable insights into optimizing the application of Bacillus subtilis ZY1 in laying hen management practices.